2008
DOI: 10.1007/s10350-008-9297-1
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Significance of RON and MET Receptor Coexpression in Patients with Colorectal Cancer

Abstract: The crosstalk between RON and MET in colorectal cancer seems important. Evaluating the expression patterns of RON and MET was predictive of clinical outcome for patients with colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 31 publications
(43 reference statements)
2
61
2
Order By: Relevance
“…Patients with tumors coexpressing MET and MST1R reportedly have a worse prognosis than those with single receptor-positive tumors. 34,62,63 The synergistic effect of MET and MST1R might induce a favorable outcome, as MET expression is associated with a better prognosis in cHL.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with tumors coexpressing MET and MST1R reportedly have a worse prognosis than those with single receptor-positive tumors. 34,62,63 The synergistic effect of MET and MST1R might induce a favorable outcome, as MET expression is associated with a better prognosis in cHL.…”
Section: Discussionmentioning
confidence: 99%
“…RON modulates diverse processes involved in tumor progression and metastasis in a variety of human cancers (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Consequently, an understanding of the molecular alterations of RON that facilitate tumor progression and metastasis will provide insight into approaches to optimized target therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic mouse models overexpressing RON in lung or mammary epithelial cells develop lung and breast carcinomas and are associated with metastatic dissemination (20,21). RON is overexpressed in a variety of human epithelial cancers including breast, colon, lung, ovary, pancreas and bladder (22)(23)(24)(25)(26)(27). Moreover, RON overexpression is associated with poor survival as well as metastasis in breast, colon and bladder cancers (22,23,27).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RON and Met concomitant overexpression is detected in many tumor types. 65,68 Lee et al 66 found that overexpression of RON and c-Met in CRC is associated with a remarkably poor clinical outcome and short-term disease-free survival. Various mechanisms underlay on abnormal expression and activation of c-Met and RON such as gene amplification, enhanced TK activity due to point mutations, and aberrant splicing of RON.…”
Section: C-met and Ron Receptorsmentioning
confidence: 99%